The Learning of Hybrid Methods to Improve Mathematics Critical Thinking Ability of Students Class XI MIPA - Pungky Rahmawati; I Nengah Parta; Hendro Permadi (Universitas Kanjuruhan Malang, 2022)
This study aims to analyze the implementation of hybrid learning to improve the critical thinking skills of mathematics students of class XI MIPA. The method used in this study is class action research using two cycles design. The subjects of this study were teachers and 12 students of class XI MIPA at SMA Brawijaya Smart School (BSS) Malang. The sampling technique used in this study was the purposive sampling technique. This study used two data collection methods, observation, and interviews used for qualitative data, then tests used for quantitative data. The instruments used are observation sheets, interview guidelines, and learner critical thinking test sheets. The data analysis techniques in this study are coding for qualitative data and descriptive statistics for quantitative data. The results showed that mathematics learning with a hybrid learning method consisting of asynchronous and synchronous learning pairs, can improve students' mathematical critical thinking skills. Therefore, this research can be used as a reference for teachers in mathematics learning with a hybrid method that is even more varied, even though constrained by pandemic conditions and remains limited in face.